Recovery of synthetic dye red 3BS from simulated wastewater using supported liquid membrane process containing immobilized kerosene-tridodecylamine liquid membrane - Othman, Norasikin (Penerbit UTM Press, 2015)
The discharge of reactive dyes into the environment has led to the toxicity problems especially to the aquatic organism. Therefore, there is a necessity for treatment of the reactive dyes from wastewater. In this work, Red 3BS reactive dye was separated using supported liquid membrane process. Commercial polypropylene (PP) membrane was used as a support of kerosene-tridodecylamine liquid membrane. Several important parameters such as flow rate, pH of feed phase, initial concentration of feed phase and stripping agent concentration were investigated. The result shows that for 50 ppm Red 3BS solution containing 0.00001M Na2SiO3 almost 100 and 89% of Red 3BS was removed and recovered respectively at the favorable condition of 0.1 M NaOH as a stripping agent, pH 3 of feed phase and 100 ml/min of flow rate.